The Frangipani Aromatherapy Usage and Anxiety Levels among Spa Visitors: An Observational Study at Padma Resort Ubud - Valerie, Regina; Winaya, I Made Niko; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : Anxiety is a typical emotional response to daily pressures experienced across various age groups, from adolescents to adults. Over 14 million people in Indonesia, or 6% of the country's population, suffer from anxiety. Kaplan and Sadock suggest that individuals aged between 21 and 45 years are more likely to experience anxiety disorders. Frangipani flowers, abundant in Bali, possess relaxation effects that can alleviate stress, attributed to compounds such as triterpenoids, amyrin, geraniol, citronellol, and linalool. Method : The research design employed was cross-sectional. The study was conducted from March to November 2023. Subjects were selected using consecutive sampling techniques. The study included 40 female spa visitors aged 21-45 years. The Zung Self-Rating Anxiety Scale was used to measure anxiety levels. Results : Based on Spearman Rho test results, a p-value of 0.000 with p<0.05 was obtained, indicating a significant relationship between frangipani aromatherapy usage and anxiety levels. The findings revealed that among visitors who underwent treatment with frangipani aromatherapy, eight individuals (40%) experienced mild anxiety, six individuals (30%) experienced moderate stress, and four individuals (20%) experienced severe anxiety. Conclusion : This study concludes that frangipani aromatherapy usage is associated with decreased anxiety levels among visitors at Padma Resort Ubud Spa, based on statistical data analysis showing p<0.05.   Keywords: frangipani, anxiety, visitors, spa